The Breath of Sense: Language, Structure, and the Paradox of Origin (Konturen, 2010)
Within contemporary analytic philosophy, at least, varieties of “naturalism” have attained a widespread dominance. In this essay I suggest, however, that a closer look at the history of the linguistic turn in philosophy can offer helpful terms for rethinking what we mean in applying the categories of “nature” and “culture” within a philosophical reflection on human life and practice. For, as I argue, the central experience of this history—namely, philosophy’s transformative encounter with what it envisions as the logical or conceptual structure of everyday language – also repeatedly demonstrates the existence of a fundamental aporia or paradox at the center of the claim of language upon an ordinary human life. I discuss the occurrence of this aporia, and attempts to resolve it, in the philosophical writing of Carnap, Quine, Wittgenstein, Heidegger, and McDowell. I conclude that the prevailing naturalistic style in analytic philosophy, whatever its recommendations, is itself the outcome of an unsuccessful attempt to resolve the central aporia of twentieth-century philosophical reflection on language. Closer attention to this aporia reveals that language, as we find it in both theoretical and everyday reflection, is in the most important sense, neither essentially “natural” nor “cultural.”